Verification Of Molecular And Conventional Techniques Used In The Diagnosis Of Equine Herpes Virus In Some Egyptian Governorates - Morcos Ibrahim Yanni (Egyptian Society for Animal Management, 2021)
Equid herpesviruses (EHVs) affect equine health and can cause signiﬁcant economic losses to the equine industry worldwide. In the current study, the circulation of two infectious equid herpesviruses (EHV-1 and EHV-4) among different horse populations in some farms was monitored. In the present study, 50 samples of nasal secretions and tissue homogenates from neurological disease cases, abortion, neonatal foal deaths, and 36 serum samples. Samples of swabs and organs inoculated in embryonated chiken egg and Madin darby bovine kidney cell line. 29samples were positive in egg injection but no detected CPE in cell line for three passages. DNA was extracted and subjected to conventional PCR to detect the two herpesviruses' presence using speciﬁc primers. Three isolates of EHV-1 and four were detected. One EHV-1 and two EHV-4 were subjected to phylogenetic analysis. Phylogenetic analysis confirmed the existence of the isolated EHV-1 and EHV-4. They were more closely related to other previously isolated EHV-1 and EHV-4 from Egypt and other countries. Antibodies against EHV-1 and EHV-4 were tested using ELISA. The results showed that EHV-1 and EHV-4 are endemic and can be a continuous threat for horses in the absence of vaccination programs and frequent virus reactivation.